2017
DOI: 10.24042/febi.v2i2.1894
|View full text |Cite
|
Sign up to set email alerts
|

Causality Relationship between Interest Rate of Deposit Banks and Profit Share Rate of Islamic Banks in Turkey

Abstract: The popularity of Islamic banking is increasing day by day. On the other hand, some people also criticized this system in some aspect. One of the criticism is that profit sharing rates of Islamic banks are similar to interest rate of deposit banks. While considering this issue, this study aims to identify the causality relationship between profit sharing rate and interest rate in Turkey. Within this scope, monthly, quarterly, 6-months and yearly data for the period between 2000 and 2016 was analyzed separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…Sukuk does not affect economic growth caused by investors' decisions to invest in sukuk (Azouzi and Echchabi, 2013). When investors take their investments and/ or new investors invest short-term sukuk, they will not be productive because sukuk, especially project-based sukuk, takes a very long time to be productive towards increasing economic growth (Yuksel et al 2017;Benbekhti et al, 2019). According to Benbekhti (2019), the transfer was a form of government expenditure to finance economically-feasible projects but it was not enough to force investors in important projects by reducing budget deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Sukuk does not affect economic growth caused by investors' decisions to invest in sukuk (Azouzi and Echchabi, 2013). When investors take their investments and/ or new investors invest short-term sukuk, they will not be productive because sukuk, especially project-based sukuk, takes a very long time to be productive towards increasing economic growth (Yuksel et al 2017;Benbekhti et al, 2019). According to Benbekhti (2019), the transfer was a form of government expenditure to finance economically-feasible projects but it was not enough to force investors in important projects by reducing budget deficits.…”
Section: Discussionmentioning
confidence: 99%
“…When we examined the academic studies of participation banks in Turkey we came to know that, the causality relationship between profit share rates and deposit interest rates, the effects of macroeconomic changes on participation banks, the analysis of deposit returns and the risk of interest rates on participation banks have been investigated (Charap and Cevik, 2011;Sarac and Zeren, 2015;Ata et al, 2016;Aysan et al, 2017;Yuksel et al, 2017;Tekin et al, 2017;Minny and Gormus, 2017;Koc, 2018;Dinc, 2019). Saleh and Zeitun (2006), Erturk and Yuksel (2013), Gokalp (2014), and Eyceyurt and Gungor (2016) investigate the participation banks' profitability in pre and post-crisis periods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Çetin's (2017) study, which used simulation, compared the deposit-interest and profit-share rates of the 2005-2015 period for a Turkish sample and arrived at the result that profit shares present higher yields. Yüksel et al (2017) dealt with the causal relationship between interest and profit-share rates on studies investigating Turkey in particular. The result of the study, which examined the period of 2000-2016, showed the relationship between deposit interest and profit shares to be strong.…”
Section: Literature Reviewmentioning
confidence: 99%